ANALYSIS OF THE EFFECTIVENESS OF THE PROCEDURE FOR APPLYING MOTOR VEHICLE TAX MUTATIONS BETWEEN DISTRICTS AND CITIES AT BANTEN PROVINCES IN SAMSAT PANDEGLANG - Sri Tjahjono, Mazda Eko; Pratiwi, Refi; Haryono, Selly Anggraeni; Shahida, Aufa Azwa (Management Science Research Journal, 2023)
The research to explore the effectiveness of Submitting Vehicle Tax Mutations Motoring between districts and cities at Banten provinces in Samsat Pandeglang can be said to be good. The research methods using the descriptive analysis to explain the procedure for applying a mutation of motor vehicle. The procedure is carried out by filling out a form, bringing the original STNK, original BPKB, bringing proof of payment PKB/BBNKB and SWDKLLJ with SKPD (regional tax assessment letter) which has been validated for the last year and bringing proof of the results physical check of the vehicle. Obstacles that occur when changing a motor vehicle's STNK and PLAT usually occur because taxpayers lose their STNK or leasing occurs, therefore they have to carry out the name transfer fees and motor vehicle tax transfers. It is concluded that the application for motor vehicle tax transfers between districts and cities at Banten provinces is the transfer of the owner's address from one province to another, which aims to clarify the identity of the vehicle